2021
DOI: 10.1177/2333794x20982433
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Adverse Childhood Experiences and Resilience With Health Outcomes in Adolescents: An Observational Study

Abstract: The relationship between Adverse childhood experiences (ACEs), resilience, and health outcomes has not been as thoroughly studied in adolescents. Adolescents completed the ACEs Questionnaire and a validated resilience measure (Child Youth Resilience Measure, or CYRM). Poor health outcome was having 1 or more: obesity, hypertension, and/or depression. 34.5% of teens had a poor health outcome, 38.6% had ACE scores of 4 or more, and resilience ranged from 45 to 84 (mean = 74.6). By univariate and bivariate analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Nine cross-sectional studies and one longitudinal study examined resilience and psychopathology in the context of adverse childhood experiences (ACE) and negative life events [ 18 ▪ , 19 , 20 ▪ , 21 ▪ , 22 ▪ , 23 , 24 , 25 , 26 ▪ , 27 ]. Overall, these studies show that higher levels of resilience are associated with mental health.…”
Section: Part Ii: Systematic Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine cross-sectional studies and one longitudinal study examined resilience and psychopathology in the context of adverse childhood experiences (ACE) and negative life events [ 18 ▪ , 19 , 20 ▪ , 21 ▪ , 22 ▪ , 23 , 24 , 25 , 26 ▪ , 27 ]. Overall, these studies show that higher levels of resilience are associated with mental health.…”
Section: Part Ii: Systematic Literature Searchmentioning
confidence: 99%
“…Five studies demonstrated the importance of investigating different components of resilience – for example, individual, relationship with a caregiver and educational support – in relation to ACEs and mental health in children and adolescents [ 18 ▪ , 19 , 20 ▪ , 23 , 24 ]. A retrospective file review in 176 children referred to a Child Abuse Service [ 18 ▪ ] found that protective factors (individual items: personal skills, peer support and social skills; caregiver: physical and psychological caregiving; and context: educational support) moderated the association between adversity and trauma-related distress.…”
Section: Part Ii: Systematic Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies found consistent evidence that resilience acts as a buffer between ACEs and psychological distress (Beutel et al, 2017), depression (Poole et al, 2017; Young-Wolff et al, 2019; Youssef et al, 2017), mood swings (Poole et al, 2017), and substance abuse (Wingo et al, 2014). Previous studies also found that higher levels of resilience predict less depression in adolescence (Freeny et al, 2021; Meng et al, 2018), and lower negative health outcomes (Hall et al, 2021). Adolescents with a history of multiple ACEs were more likely to be less resilient (Ding et al, 2017).…”
Section: Introductionmentioning
confidence: 85%
“…These findings are consistent with previous studies which found that adolescents with higher ACEs scores had higher negative health risks, and higher resilience scores were associated with a lower risk of negative health outcomes (suicide, sadness, and/or depression anxiety). For example, Hall's study found that ACEs and resilience were inversely related (Hall et al, 2021). A meta-analysis of outcome reporting (≥ 1 ACEs vs. no ACEs) found that persons with a history of ACEs were 63% less likely to demonstrate high resilience compared to those with no history of ACEs (Morgan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%